Impact of interventions promoting condom use among HIV-infected individuals - Silveira, Mariângela F; Santos, Iná dos (Revista de Saúde Pública, 2005)
In order to identify educational interventions promoting male condom use during intercourse among HIV+ persons, we conducted a systematic review of publications. Lilacs/Bireme, Medline and Popline data sets and CDC and UNAIDS sites were searched without time limit. Uniterms used were: women; men; interventions; HIV; Aids; HIV positive; risk behaviors; sexual risk behaviors; and intervention studies. Fourteen interventions were included, eight of which reported a positive result. Most frequent methodological weaknesses observed were lack of randomization, no control for confounding, high rates of losses to follow-up, small sample sizes, and outcome of condom use stated by patient self-report. Publication bias favoring studies showing a beneficial effect has to be considered. Effective interventions aiming to promote condom use among HIV positive persons are currently an important tool in the prevention of HIV dissemination.